2022
DOI: 10.1002/smll.202207017
|View full text |Cite
|
Sign up to set email alerts
|

A Microfluidic Contact Lens to Address Contact Lens‐Induced Dry Eye

Abstract: The contact lens (CL) industry has made great strides in improving CLwearing experiences. However, a large amount of CL wearers continue to experience ocular dryness, known as contact lens-induced dry eye (CLIDE), stemming from the reduction in tear volume, tear film instability, increased tear osmolarity followed by inflammation and resulting in ocular discomfort and visual disturbances. In this article, to address tear film thinning between the CL and the ocular surface, the concept of using a CL with microc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Zhu et al addressed this issue by developing an eye-blink mimicking system using a microfluidic hydrogel with integrated microchannels. 214 Their in vitro study demonstrated that the system could enhance tear transport from the pre-lens tear film to the post-lens tear film by simulating the motion of an artificial eyelid in a pressure range similar to that of human eyelid pressure. The microchannels were made of poly(2-hydroxyethyl methacrylate) (poly(HEMA)).…”
Section: Tearsmentioning
confidence: 99%
“…Zhu et al addressed this issue by developing an eye-blink mimicking system using a microfluidic hydrogel with integrated microchannels. 214 Their in vitro study demonstrated that the system could enhance tear transport from the pre-lens tear film to the post-lens tear film by simulating the motion of an artificial eyelid in a pressure range similar to that of human eyelid pressure. The microchannels were made of poly(2-hydroxyethyl methacrylate) (poly(HEMA)).…”
Section: Tearsmentioning
confidence: 99%
“…Water-soluble glue was employed to secure the poly(HEMA) film onto the planner substrate, enabling the production of high-quality microfluidic channels. 68,69 Light or heat mediated therapy is an important application of smart contact lenses in the treatment of eye diseases, and the preparation of component materials in this respect is also a hot spot of scientific research. 70−72 Figure 4d shows the main device used for ocular hyperthermia.…”
Section: ■ Primary Formsmentioning
confidence: 99%
“…This microfluidic contact lens utilizes a UV-curable biomaterial with excellent biocompatibility, mechanical properties, and hydrophilicity, enabling automatic collection and monitoring of tears. 40,69,95 ■ THE INTEGRATION OF MICROFLUIDICS Microfluidics has the advantages of excellent stretchability, a fine microstructure, high integration of multiple functions, and low cost and has been widely used in wearable devices. Welldesigned microfluidic devices enable outstanding versatility in wearable applications, including sample collection, processing and storage, sample analysis, signal conversion and amplification, mechanical sensing, and power supply.…”
Section: ■ Primary Formsmentioning
confidence: 99%
“…Skin surface contamination, old and new sweat mixing problems: The skin may be contaminated by dead skin cells, sebum, the condensate from trans-epidermal water loss, and other contaminants induced by human activities or environmental exposure. The combination of flexible microfluidics with well-sealed microchannels or microchambers has been applied to harvest sweat to decrease contamination and evaporation of sweat samples (similar to wearable tear analysis) [60][61][62]. In addition, patterned hydrophilic fillers were designed to realize rapid sweat uptake at low secretion rates.…”
Section: Current Challenges and Future Perspectives For The Wearable ...mentioning
confidence: 99%